ON ARMENIA’S POSSIBLE WITHDRAWAL FROM THE CSTO IN THE CONTEXT OF ANTI-TERROR FIGHT - Raul I. Khabibullin (Научно-аналитический вестник Института Европы РАН)
In recent years, relations between Armenia and the Collective Security Treaty Organization (CSTO) have deteriorated due to its refusal to provide military assistance to Yerevan during the recent clashes with Azerbaijan. The growing disagreements between Yerevan, on the one hand, and the CSTO and Moscow, on the other, have led to the fact that recently Armenia has not participated in the functioning of the organization and has repeatedly stated that it is ready to leave it. The article aims to determine the consequences of Armenia’s possible withdrawal from the CSTO for the anti-terrorist potential of this organization. The article provides an analysis of Armenia's historical role in the collective security system, as well as Yerevan’s actions to freeze its membership in the CSTO, outlines the priorities and goals of other influential members of the international community (Russia, the United States, and the EU) in relation to the South Caucasus, and defines the prospects for the organization's work in the current conditions. It is concluded that Armenia’s withdrawal will not have a significant impact on the work of the CSTO, but will weaken the overall regional security system, increasing the terrorist threat not only to other post-Soviet states, but also to Armenia itself.